TOWARDS A HOLISTIC CUSTOMER EXPERIENCE MANAGEMENT FRAMEWORK FOR ENTERPRISES - du Plessis, Liezl; de Vries, Marne (The South African Journal of Industrial Engineering, 2016)
We have entered the age of the customer where customer choice is the main differentiator between enterprises. Therefore, enterprises need to shift their focus to customer experience management (CEM). A survey conducted within the telecommunications sector indicated a gap between theoretical CEM approaches and their implementation in enterprises. Although a systematic literature review and inductive thematic analysis of CEM literature revealed nine common themes, none of the existing approaches includes all of these themes in a comprehensive way. Based on those nine themes, this paper presents a new holistic framework for CEM that managers and practitioners concerned with improving customer experiences could use.